Comparison of the Antibacterial Effectiveness of Kersen Leaf Extract and Cassava Leaf Extract Against Escherichia coli and Staphylococcus aureus: A Literature Review - Muhammad Rofif Albukhori; Dia Septiani; Hilmah Ayu Mardhiyya (Jurnal Biologi Tropis, 2026)
Staphylococcus aureus and Escherichia coli are among the most common bacterial pathogens responsible for various infectious diseases, prompting the search for alternative antibacterial agents from medicinal plants. Cassava (Manihot esculenta Crantz) and cherry (Muntingia calabura L.) leaves contain bioactive compounds, including flavonoids, tannins, and saponins, that exhibit antibacterial properties. This study aimed to compare the antibacterial effectiveness of cassava and cherry leaf extracts against S. aureus and E. coli through a systematic literature review. Articles were retrieved from the Google Scholar and PubMed databases following predefined inclusion and exclusion criteria. Of the 1,072 records identified, 12 eligible studies were included in the final synthesis. The reviewed studies consistently demonstrated that both plant extracts inhibited the growth of S. aureus and E. coli. However, cherry leaf extract generally exhibited stronger and more consistent antibacterial activity than cassava leaf extract, both as crude extracts and in topical formulations. The superior activity of cherry leaves was associated with their higher abundance of antibacterial phytochemicals and broader inhibitory spectrum. These findings suggest that cherry leaf extract has greater potential as a natural antibacterial agent, although further in vivo studies and clinical evaluations are required to confirm its efficacy and safety for therapeutic applications.